Late results of bioabsorbable scaffolds implanted in spontaneous coronary artery dissection evaluated with computed tomography coronary angiography. (25th November 2020) - Pozo Osinalde, E; Macaya, F; Camacho-Freire, S.J; Massot, M; Moreu, J; Suarez De Lezo, J; Ortas-Nadal, M.R; Salinas, P; Diaz-Fernandez, J.F; Gonzalez-Colino, R; Gonzalo, N; Gomez De Diego, J.J; et al.
Abstract: Background: Percutaneous coronary intervention (PCI) in spontaneous coronary artery dissection (SCAD) should be reserved for cases presenting with ongoing extensive ischaemia. Bioresorbable scaffolds (BVS) have emerged as an alternative to avoid permanent stenting, an especially attractive concept for this clinical scenario. However, data of late angiographic outcome of this device in SCAD is lacking. Purpose: To evaluate the long-term angiographic outcome of BVS in the setting of SCAD using computed tomography coronary angiography (CTCA) Methods: In this multicentre prospective study, high-risk SCAD patients treated with BVS were scheduled for a follow-up CTCA at least 2 years from implantation date. Acquisition was performed according to the current recommendations. All the studies were analysed in a central core laboratory by an independent level 3 expert in CTCA blinded to the clinical and angiographic results. For this purpose, a dedicated software for coronary analysis was used to quantify coronary stenosis and evaluate coronary wall. Results: Thirty-four BVS were implanted in 15 SCAD patients (51±12 years-old; 87% female) from 7 different centres in Spain and United Kingdom. The most common presentation was STEMI (n=9, 60%). Target vessels included 11 left anterior descending arteries (73.3%), 3 right coronary arteries (20%) and 1 left circumflex coronary artery (6.7%). One patient received target lesion revascularisation due to scaffold shrinkage in a proximal right coronary artery at 13 months. CTCA was performed 2.4±0.7 years after BVS implantation. No scaffold thrombosis or significant stenosis were detected. Patency of all scaffolds was confirmed with a median luminal area of 5.52 mm 2 (IQR: 3.74–6.95) and median stenosis of 11% (IQR: 4–15%). Regarding coronary wall tissue characterization of segments with BVS, there was 32±9.3% of plaque burden and a median plaque volume of 45.3 mm 3 (IQR: 26.6–61.9). The most common component of the plaque was fibrous (85±9.4%). Compared to the proximal reference segments, BVS showed more plaque burden (32.2% vs 25.3%; p=0.017) and fibrous percentage (84.7% vs 75.1%; p=0.004) whereas less fibrofatty (6 vs 4.8 mm 3 ; p=0.007) and necrotic volume (0.4 vs 1.2 mm 3 ; p=0.029). BVS segments showed lower absolute minimal luminal area (5.5 vs 8.9 mm 2 ; p=0.004) and diameter (2.7 vs 3.4 mm; p=0.004) compared to the reference segment; however, non-significant differences were seen in percentage stenosis, in keeping with normal vessel tapering. Conclusions: In this series of SCAD treated with BVS, scaffolds showed a satisfactory late angiographic outcome, with no significant restenosis and an excellent minimal luminal area and optimal coronary wall healing observed. Funding Acknowledgement: Type of funding source: None